Inclusive institutions and local economic evolution: Perspectives from Guayaquil and Quito. (August 2019) - Freire-Gibb, L Carlos; Tapia Carrillo, Luis
Urbanization is often related to better economic and living standards and, according to the United Nations, by the mid-21st century, 70% of humankind will live in urban areas. Currently, roughly 80% of the populations in North and South America are urbanized, compared to the global average of 55%. Meanwhile, inequality has also been increasing swiftly, and Latin America is among the most unequal regions in the world. With global urbanization and inequality trends rising, examining the urban areas of a Latin American country could shed light on potential evolution paths. Hence, this article outlines the social and economic evolution of Guayaquil and Quito, the two primary cities of Ecuador. In the 20th century, Guayaquil had economic and demographic advantages; however, Quito has since surpassed Guayaquil on several social, demographic and economic indicators. This article suggests that Guayaquil's relative stagnation is due to an institutional framework favouring the economic and political elites and supports the argument that inclusive local processes and governance (or the lack thereof) can support (or hinder) local economic development.